Solar heater system implementation as a front step in Overcoming the global warming issues : case studies in Seberang Perai Selatan, Penang. - Lee , Li Li; Abdullah, Aldrin (2008)

(untitled)
The major purpose of this study on solar heater system implementation in Seberang Perai Selatan, is to identify the level of preference and satisfaction from questionnaires answered by the respondents ( the residents equipped with the solar heater system package) and the residents who stay around the case studies area, on the implementation solar heater in the residential housing properties. The importance of the solar heater system implementation in overcoming the global warming and the efforts of the society in playing part of the role in overcoming the global warming. As part conclusion of the work, to describe that even in the urban planning, by implementing the package comes with energy saver such as solar heater system in supplying hot water through the solar panels absortion of the direct sunlights without consumption of the electricity supply ,this has bring cost savings , reduction of the kilowatts electricity supplies and overall environmental heat to the mankind. D.M., ( 2008) claimed that solar power still untapped in Malaysia, more awareness and renewable energy plans shall be carried out by the authorities and the public societies , as possible future positive impacts come from our current positive actions.